2020
DOI: 10.1101/2020.08.05.229294
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Physioxia stimulates extra-cellular matrix deposition and increases mechanical properties of human chondrocyte-derived tissue-engineered cartilage

Abstract: Cartilage tissue has been recalcitrant to tissue engineering approaches. In this study, human chondrocytes were formed into self-assembled cartilage sheets, cultured in physiologic (5%) and atmospheric (20%) oxygen conditions and underwent biochemical, histological and biomechanical analysis at one- and two-months. The results indicated that sheets formed at physiological oxygen tension were thicker, contained greater amounts of glycosaminoglycans (GAGs) and type II collagen, and had greater compressive and te… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…The results show a significantly increased cell expansion rate between all three test conditions (SCM, SCM + bFGF, bFGF) and the control (TCP) (p < 0.0001), sustained throughout the four passages. This is consistent with our previous work that has shown enhanced growth of chondrocytes with the use of SCM compared to TCP (Kean et al, 2019;Dennis et al, 2020). In addition, chondrocytes cultured in SCM + bFGF showed a significantly higher expansion rate than in bFGF alone in all four passages, indicating that there is some additional benefit to including both components.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The results show a significantly increased cell expansion rate between all three test conditions (SCM, SCM + bFGF, bFGF) and the control (TCP) (p < 0.0001), sustained throughout the four passages. This is consistent with our previous work that has shown enhanced growth of chondrocytes with the use of SCM compared to TCP (Kean et al, 2019;Dennis et al, 2020). In addition, chondrocytes cultured in SCM + bFGF showed a significantly higher expansion rate than in bFGF alone in all four passages, indicating that there is some additional benefit to including both components.…”
Section: Discussionsupporting
confidence: 91%
“…This increase in types I and X collagen and a decrease in type II were most apparent in the TCP group. In a previous work, it was observed that the type I collagen in our tissue-engineered cartilage reduced with increased culture time to 2 months, something we did not investigate here (Dennis et al, 2020).…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…MSCs have also shown increased ECM production when cocultured with chondrocytes [203]. Both MSCs [203] and primary articular chondrocytes [54] have a high level of donor to donor variability. This variability is a disadvantage in using cells from any primary source.…”
Section: Cells Used In Cartilage Bioprintingmentioning
confidence: 99%